'In search of excellence' or 'stuck in the middle'? The quest to build a (more) entrepreneurial third-generation university. (1st January 2013) - Ylinenpää, Håkan
Organisational ambidexterity, defined as an organisation's ability to be aligned and efficient while simultaneously adapting to changes in the environment, has gained increasing interest in recent years. Elaborating on knowledge-based organisations such as universities, this paper questions the normative and simple advice on how to develop successful entrepreneurial organisations (in this case: universities) and advocates that managing ambidexterity in an increasingly knowledge-based economy is a key to understanding this phenomenon better. Using Luleå University of Technology (LTU) as an empirical example, this paper elaborates on the managerial challenges involved in developing applied knowledge for practice and at the same time aiming for academic excellence as a base for a (more) entrepreneurial, third-generation university.